Potentials for Electric Vehicles in France, Germany, and India - Kathrin Dudenhöffer; Rahul Arora; Alizée Diverrez; Axel Ensslen; Patrick Jochem; Jasmin Tücking (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2014)
As road transport is responsible for a major part of greenhouse gas emissions, broad diffusion of electric vehicles (EV), in combination with electricity generated from "clean" energy sources, can contribute to reducing overall CO2 emissions significantly. EV include plug-in hybrid electric vehicles (PHEV) and range-extended electric vehicles (REEV) which still contain a combustion engine and, hence, do not restrict the user compared to conventional vehicles, as well as pure battery electric vehicles (BEV). BEV will be focused in this article, as the user behavior is affected considerably by a limited range and longer "refueling" times. However, with a current market penetration below 1 %, the impact of BEV is marginal. Although the sales figures of BEV are low all over the world, it will be pointed out in this article that the potential for diffusion and take-off of this new technology varies in different countries depending on some framework conditions like infrastructure and energy generation as well as on individual factors measured by surveys in the different countries. Hence, this study tries to compare market potentials for BEV in different countries in order to improve the knowledge basis for decisions of policy makers. Two Western countries, France and Germany, and one rapidly growing developing country, India, have been chosen. In the first step of our analysis, framework conditions are analyzed and compared, which influence societies' strategies as regards future developments of national passenger transport systems determining the future role of BEV. This step focuses on economic differences, greenhouse gas emissions, national EV promotion programs, differences in the underlying electric power system, as well as passenger car stock and vehicle (including motorized two-wheeler) registrations. The second step concentrates on the differences in user acceptance of BEV in the three different nations. Therefore, consumers' responses to internet questionnaires relating to BEV acceptance which were distributed in France, Germany and India were compared. With the help of variance analysis statistical differences of consumers' statements in the three countries are determined. The main result of the two-step analysis is that France currently has the biggest market potential for BEV, since the economic conditions and acceptance patterns in society are more beneficial for BEV than they are in Germany and India. While the individuals' BEV acceptance level seems to be comparably lower in Germany, Indian framework conditions negatively influence the diffusion of BEV. Thus, it seems advantageous to start promoting BEV in France, to focus on REEV and PHEV in Germany, and to neglect promoting policies for (four-wheel) EV in India in the next years. However, it seems necessary to support long-term diffusion of EV in India, considering the increasing sales figures of new vehicles and the corresponding challenges in Indian megacities.
urn:nbn:de:swb:90-436794
Keywords: 330; Electric vehicle; market potential; market comparison; Germany; France; India